Aerosol particles deposition and distribution in bifurcating ventilation ducts - Miguel, A. F. (2012)
The quantitative information gained from detailed studies of particle deposition in ducts is important, for example, to evaluate human exposure to particles within buildings, implement cleaning strategies for ventilation ducts and also understand particulate deposition in the respiratory tree. For this purpose, an experimental study for aerosol particles of diameters ranging from 8.1 to 23.2 m was conducted in a curved bifurcating ventilation duct. At the bend segment of the duct, the particle size, bend angle, curvature ratio and Reynolds number affect aerosol deposition signiﬁcantly. On the other hand, tests conducted on the bifurcating segments show that deposition increases with particle size and Reynolds number. Accumulation of particles occurs mainly around the bend segment and the ridge of carina of the bifurcation. In all segments of the duct models, particle deposition is found to be enhanced with increasing humidity which increases from 66 to 95% (i.e., close the saturation). A physical interpretation of the results obtained is also presented.